Prevalence of Gestational Diabetes Mellitus in Nepal: A Systematic Review and Meta-analysis - Pokharel, Pashupati; Pokhrel, Kailash Mani; Lamichhane, Pratik; Khanal, Kapil; Rawal, Suniti (Journal of Nepal Health Research Council, 2022)
Background: Gestational diabetes mellitus is a condition of glucose intolerance during pregnancy. The burden of Gestational diabetes mellitus is ever increasing including a lower middle-income country like Nepal. Methods: This meta-analysis was conducted in accordance to the guidance of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Databases of “Embase”, “Google Scholar”, “Scopus”, “Web of Science” were searched for observational studies in Nepal from 2000 to July 2021. Random effect model was used to estimate the pooled prevalence subgroup analysis.Results: This systematic review and meta-analysis analyzed 9 studies with a total of 20865 participants. Pooled prevalence of gestational diabetes mellitus was 2.61% (95% CI: 1.25- 5.37). From subgroup analysis, the prevalence of Gestational diabetes mellitus according to the diagnostic criteria were: International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria 6.56% (95% CI: 4.79-8.92), World Health Organization (WHO) criteria 4.81% (95% CI: 3.79-6.08), Diabetes in Pregnancy Study Group of India (DIPSI) criteria 4.71% (95% CI: 3.06-7.18), Carpenter and Coustan criteria (CC) 1.08% (95% CI: 0.43-2.71); prevalence according to the publication time: before 2015 1.20% (95% CI: 3.64-6.41), in and after 2015 4.84% (95% CI: 0.42-3.39); prevalence according to the place: within Kathmandu valley 2.70% (95% CI: 1.17-6.08), outside Kathmandu valley 2.28% (95% CI: 0.26-17.15).Conclusion: Our study revealed the increasing prevalence of GDM in Nepal. Further large observational studies at local levels are essential to measure the actual burden, risk factors and potential preventive measures for Gestational diabetes mellitus. Keywords: Diabetes in pregnancy; gestational diabetes mellitus; meta-analysis; Nepal; prevalence.